2007
DOI: 10.1177/0963662506071287
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from 25 years of PUS survey research? Liberating and expanding the agenda

Abstract: This paper reviews key issues of public understanding of science (PUS) research over the last quarter of a century. We show how the discussion has moved in relation to large-scale surveys of public perceptions by tracing developments through three paradigms: science literacy, public understanding of science and science and society. Naming matters here like elsewhere as a marker of “tribal identity.” Each paradigm frames the problem differently, poses characteristic questions, offers preferred solutions, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
477
1
60

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 594 publications
(544 citation statements)
references
References 59 publications
6
477
1
60
Order By: Relevance
“…He assumes that this failure to hold what he considers to be the obviously correct view must be due to public ignorance or misunderstanding [8]. The results of this survey can instead be read as evidence that people are taking the time and effort to reflect properly on a question that is complicated and interest laden.…”
mentioning
confidence: 97%
“…He assumes that this failure to hold what he considers to be the obviously correct view must be due to public ignorance or misunderstanding [8]. The results of this survey can instead be read as evidence that people are taking the time and effort to reflect properly on a question that is complicated and interest laden.…”
mentioning
confidence: 97%
“…But such surveys have been interpreted as the 'cognitive deficit approach' which contrasts scientists against less informed lay people (Wynne, 1982;Ziman, 1991). Bauer et al (2007) suggested a reframing of the knowledgeattitude problem recognising that information matters not only as the ability and motivation to process it (see also Sturgis and Allum, 2004), but also as a marker of quality of the attitude.…”
Section: Knowledge Evaluative Attitudes Religiosity and Trustmentioning
confidence: 99%
“…Central to the foundation of the public understanding of science approach in science communication is experts' assumption that unfavourable attitudes can be countered by providing knowledge, an assumption that remains popular today (Ahteensuu, 2012;Bauer, 2016). Educating the public, however, has proved ineffective in creating more favourable public attitudes (Bauer, Allum, & Miller, 2007). Another view that remains popular among experts is that people remain ignorant (or unknowledgeable) because they are too passive or too lazy to take an interest in science (Ahteensuu, 2012;Bucchi, 2008).…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…Second, the deficit model continues to remain popular among technical experts and policymakers (Kerschner & Ehlers, 2016). Consequently, much current science communication is still influenced by the deficit model (Miller, 2001;Bauer, Allum, & Miller, 2007;Durant, 1999;Bauer, 2016). …”
Section: Evolution and Limitation Of The Dominant Approach In Sciencementioning
confidence: 99%
See 1 more Smart Citation